Effects of tea residues-fermented feed on production performance, egg quality, antioxidant capacity, caecal microbiota, and ammonia emissions of laying hens - Chen, Xianxin; Zhou, Xinhong; Li, Shiyi; Zhang, Huaidan; Liu, Zhenkun (Frontiers in Veterinary Science, 2023)
Abstract: This study was to assess the effects of tea residues-fermented feed (TR-fermented feed) on production performance, egg quality, serum antioxidant capacity, caecal microbiota and ammonia emissions of laying hens. A total of 1296 Lohmann laying hens have randomly distributed four groups with six parallels and fed with diets TR-fermented feed at the rates of 0 (control), 1, 3 and 5%. The inclusion of 1% (TR)-fermented feed resulted in a significant increase in egg-laying rate and average egg weight of birds, and a reduction in the feed-to-egg ratio when compared to the control group (p＜0.05). The addition of 1% and 3% of (TR)-fermented feed significantly improved the Haugh unit of eggs (p＜0.05). The eggshell thickness was observed to increase by almost one-fold upon the inclusion of 3% and 5% (TR)-fermented feed in the basal diet (p＜0.05). The supplementation of 3% (TR)-fermented feed significantly increased the content of Methionine, Tyrosine, Proline, EAA, C18:3n6, C22:0, C22:6n3, C23:0, C24:1 and ∑ω-3 PUFA in the eggs (p < 0.05). The addition of a certain amount of (TR)-fermented feed can enhance the activity of GSH-PX and SOD in chicken serum, and reduce the level of MDA (p＜0.05). The ammonia concentration in the hen house of laying hens in the treatment groups decreased significantly (p < 0.05). Bacteroidetes and Firmicutes, the main phyla in the cecal bacterial community, were differentially abundant each group, comprising greater than 55% and 33%, respectively. Collectively, This research indicates that TF supplementation improves the performance of laying hens and reduces ammonia emissions and can be used in industry-scale layer production.